First record of Alainites sadati Thomas, 1994 (Ephemeroptera: Baetidae) in Tunisia, description of the larval stage and ecology - Zrelli, Sonia; Gattolliat, Jean-Luc; Boumaïza, Moncef; Thomas, Alain (Zootaxa, 2012)
Alainites sadati Thomas, 1994 is recorded for the first time in Tunisia. The first description of the larval stage of A. sadati Thomas, 1994 is provided based on material from Algeria, near the type locality, and Tunisia. This species can be separated from the other Palaearctic species by the number of gills, the setation of the legs, the prolongation of the paraproct and the reticulation of the tergites. Based on the new data, the ecology of A. sadati is discussed.